APPLICATION OF FISHBONE ANALYSIS FOR IDENTIFYING RISKS IN HYDROPONIC LETTUCE (LACTUCA SATIVA L.) AT CV. BWS HYDROPONICS - Sri Sari Utami; Muhammad Risky (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2026)
This study aims to identify the types of defects occurring in hydroponic lettuce and to analyze their causal factors using a fishbone diagram. Data were collected through direct observation during the cultivation and postharvest stages at CV. BWS Hydroponics. The findings revealed that the most frequent defects were torn leaves (6%) and perforated leaves (2%) out of a total harvest of 1,735 leaves. The fishbone analysis indicated that these defects were influenced by three main factors: human, method, and environment. Human factors included a lack of attentiveness during harvesting and sorting, while methodological factors were related to careless packaging techniques and limited storage containers. Environmental factors contributing to defects included pest infestations, such as grasshoppers and Spodoptera litura, as well as frog-eye spot disease (Cercospora sp.), which was exacerbated by high rainfall. The results further showed that CV. BWS Hydroponics performed relatively better compared to previous studies, as only two types of leaf defects were identified. This advantage was supported by more responsive pest control and postharvest handling practices. Recommended improvements include enhancing worker skills, implementing more disciplined standard operating procedures (SOPs), selecting appropriate storage containers, adopting preventive pest control measures, and optimizing plant spacing to reduce humidity. Therefore, the comprehensive implementation of these corrective strategies is expected to improve the quality and competitiveness of hydroponic lettuce in the market.